FAIR COMPETITION THROUGH PRICE AGREEMENT BETWEEN BUSINESSMEN ASSOCIATED IN ASEAN ECONOMIC COMMUNITY - Azizah Azizah (Universitas Muhammadiyah Metro, 2018)
Fair competition is one of the keys to succeed for the fair market economic system. Through price fixing agreements between businessmen in the ASEAN countries, it will cause the market equilibrium with no ignoring the interests of businessmen and the people. Based on these issues, then the legal problems,are namely: 1) How are the health competition between businessmen in the ASEAN economic community. 2) How should the setting of price agreements between businessmen in the ASEAN economic community. This paper is a study of hermeneutics using normative approach, philosophy of law, sociology of law, comparative law and political law.The study concluded that: 1) The attempts setting of fair competition between businesses in the ASEAN economic community that need to be applied in the form of agreement, 2) In its development, price fixing agreements between businessmen that are members of the ASEAN economic community still balance with the interests of the public as consumers.